Ergogenic effects of precooling with cold water immersion and ice ingestion: A meta-analysis - Choo, H. C.; Nosaka, K.; Peiffer, J. J.; Ihsan, M.; Abbiss, C. R. (European Journal of Sport Science, 2018)
This review evaluated the effects of precooling via cold water immersion (CWI) and ingestion of ice slurry/slushy or crushed ice (ICE) on endurance performance measures (e.g. time-to-exhaustion and time trials) and psychophysiological parameters (core [Tcore] and skin [Tskin] temperatures, whole body sweat [WBS] response, heart rate [HR], thermal sensation [TS], and perceived exertion [RPE]). Twenty-two studies were included in the meta-analysis based on the following criteria: (i) cooling was performed before exercise with ICE or CWI; (ii) exercise longer than 6 min was performed in ambient temperature =26°C; and (iii) crossover study design with a non-cooling passive control condition. CWI improved performance measures (weighted average effect size in Hedges` g [95% confidence interval]?+?0.53 [0.28; 0.77]) and resulted in greater increase ( EX) in Tskin (+4.15 [3.1; 5.21]) during exercise, while lower peak Tcore (-0.93 [-1.18; -0.67]), WBS (-0.74 [-1.18; -0.3]), and TS (-0.5 [-0.8; -0.19]) were observed without concomitant changes in EX-Tcore (+0.19 [-0.22; 0.6]), peak Tskin (-0.67 [-1.52; 0.18]), peak HR (-0.14 [-0.38; 0.11]), and RPE (-0.14 [-0.39; 0.12]). ICE had no clear effect on performance measures (+0.2 [-0.07; 0.46]) but resulted in greater EX-Tcore (+1.02 [0.59; 1.45]) and EX-Tskin (+0.34 [0.02; 0.67]) without concomitant changes in peak Tcore (-0.1 [-0.48; 0.28]), peak Tskin (+0.1 [-0.22; 0.41]), peak HR (+0.08 [-0.19; 0.35]), WBS (-0.12 [-0.42; 0.18]), TS (-0.2 [-0.49; 0.1]), and RPE (-0.01 [-0.33; 0.31]). From both ergogenic and thermoregulatory perspectives, CWI may be more effective than ICE as a precooling treatment prior to exercise in the heat.